Isothermal Decomposition Kinetic Analysis of Polymethylphenylsilsesquioxane/Epoxy Resin Systems. Issue 9 (November 2014) - Wang, Jiangbo; Li, Yongyou; Jin, Yi; Wang, Zhiqiang
The decomposition kinetics of polymethylphenylsilsesquioxane/epoxy resin (PMPSQ/EP) systems under isothermal conditions was investigated by thermogravimetric analysis (TGA), and the isothermal kinetics equation was used to describe the thermal decomposition process. The results showed that the activation energy in the case of isothermal decomposition was first raised and then quickly decreased with increasing degree of conversion, both for EP and PMPSQ/EP (FREP) systems. Moreover, the activation energy of FREP in any degree of conversion was lower than that of pure EP. It was caused by the addition of PMPSQ, which accelerated thermal decomposition and promoted the formation of an insulating carbon layer. Thus, the flame-retardant performance of EP system containing PMPSQ was improved.